1996
DOI: 10.1034/j.1600-0501.1996.070306.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an endosseous titanium implant with a sandblasted and acid‐etched surface in the canine mandible: radiographic results

Abstract: Previous studies have demonstrated in short-term experiments that sandblasted and acid-etched (SLA) titanium implant had a greater bone-to-implant contact than a titanium plasma-sprayed (TPS) implant in non-oral bone. In the present study, an SLA implant was compared radiographically to a TPS implant under unloaded and loaded conditions in the canine mandible for up to 15 months. 69 implants were placed in 6 foxhounds. Standardized radiographs were taken at baseline, preload, 3, 6, 9, and 12 months of loading.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
1
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 173 publications
(124 citation statements)
references
References 0 publications
1
113
1
9
Order By: Relevance
“…Pickled and acid-etched, sand-blasted (SLA) commercially pure titanium samples were kindly provided by Straumann Institut (Basel, Switzerland) These surfaces have been extensively described and characterized in the literature 17,18) . The samples were provided as sterile discs of 1 mm thickness, 16 mm diameter, and were used in 24 well plates (Euroclone, Milano, Italy) for the biological assays.…”
Section: Titanium Surfacesmentioning
confidence: 99%
“…Pickled and acid-etched, sand-blasted (SLA) commercially pure titanium samples were kindly provided by Straumann Institut (Basel, Switzerland) These surfaces have been extensively described and characterized in the literature 17,18) . The samples were provided as sterile discs of 1 mm thickness, 16 mm diameter, and were used in 24 well plates (Euroclone, Milano, Italy) for the biological assays.…”
Section: Titanium Surfacesmentioning
confidence: 99%
“…27,28 Macroscopic characteristics of the implant surface influence cellular events present at the bone biomaterial interface and are critical for the long-term survival of the implant. 28 The cells have been demonstrated to be sensitive to microtopography.…”
Section: Implant Microdesignmentioning
confidence: 99%
“…It has been reported that sandblasted and acid-etched (SLA) titanium promotes greater osseous contact compared with titanium-plasmasprayed implants [6][7][8][9] . This is due to the high surface roughness of SLA produced by grit blasting and acid etching, with the latter resulting in an increase in sub-surface hydrogen concentration and the formation of titanium hydride 10) .…”
Section: Introductionmentioning
confidence: 99%